The Issue Of Human Rights In The Work Of Omon Matjon (Zien Journal of Social Sciences and Humanities, 2026)
This article discusses the issue of protectihg human rights, which has been one of the pressing problems since the beginning of human history. Although the “Universal Declaration of Human Rights” was adopted in 1948,the fact that human rights were still being violated in America in the 1960 s. and 1970 s.,including the fact that representatives of the wealthy class used various illegal means to subjugate the poor and materially needy people to their personal desires, was artistically expressed through the short dramatic epic “The destruction of Atlantis or american marriage” by the people’s poet of Uzbekistan Omon Matjon.The epic talks about the principle stated in the fifth article og the Declaration,‘‘…no one should be subjested to degrading treatment or punishment”